PEMBERDAYAAN SAYURAN CAISIM DALAM MENINGKATKAN UMKM DI DESA KAREHKEL - Mardiatama, Welinda; Fitria, Meliana; Ma’ruf, Samsul; Anjas, Muhammad; Ayu Yudianti, I Gusti; Rifatunnisa, Adinda; Andi Fariz, Muhammad; Rokib, Muhammad (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2024)
This research aims to improve MSMEs in Karehkel Village through empowerment in the area by carrying out innovations in the form of experiments on Caisim vegetables which are processed into Healthy Tabur Seasoning. The subjects of this research are residents of Karehkel Village, especially Caisim Vegetable Farmers. The results of this research show that MSMEs in Karehkel Village are increasing and have a positive influence on Karehkel Village. And this research shows that innovation activities in the village are sustainable